Impact of wearable-assisted walking on sarcopenia and body composition in older adults - Cheng-En Wu; Yankuba B. Manga (BMC Geriatrics)
Abstract Background Physical inactivity constitutes a global public health challenge, particularly among older adults. This study investigates the impact of a wearable device-assisted walking program on body composition, muscle strength, and sarcopenia in this population. Methods Eighty healthy older adults (40 men and 40 women), aged 65 and above, were randomly assigned to either an intervention (experimental) group, which participated in a structured walking program utilizing wearable devices, or a non-intervention (control) group, which maintained their habitual activities. The walking program spanned 12 weeks. Key assessments included body composition analysis, handgrip strength measurement, the 5× sit-to-stand test, and the appendicular skeletal muscle index (ASMI). Results The intervention group exhibited significant improvements in body composition and muscle strength. Skeletal muscle mass (SMM) increased by 5.5% (95% CI: 4.2–6.8%), handgrip strength improved by 13.1% (95% CI: 10.6–15.6%, p < 0.05), and lower limb function improved by 10.5% (p < 0.05). ASMI proved to be an effective and accessible metric for sarcopenia assessment, demonstrating strong correlations with SMM, handgrip strength, and sit-to-stand performance. Conclusions Wearable devices, such as smartwatches and fitness trackers, provide real-time feedback and enable tailored exercise recommendations, offering a practical and personalized strategy for mitigating sarcopenia. This study confirms that wearable-assisted walking programs effectively improve muscle health and functional performance in older adults, reinforcing their potential for promoting healthy aging.